APPLICATION OF EXTRACTIVE SPECTROPHOTOMETRIC METHODS FOR THE DETERMINATION OF FLUCLOXACILLIN AND TRANDOLAPRIL USING BROMOCRESOL GREEN - R, VIJAYALAKSHMI; D, SOWJANYA; S, ARCHANA; MD, DHANARAJU (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim was to develop rapid, simple, sensitive, and accurate visible spectrophotometric methods for the determination of flucloxacillin and trandolapril. Materials and Methods: These methods are based on the formation of ion-pair complex of the flucloxacillin, with bromocresol green in acidic medium. The colored products are extracted with chloroform and measured spectrophotometrically at 433 nm and 430 nm for flucloxacillin and trandolapril, respectively. Results: Beer's law was obeyed in the concentration range of 0.5-2.5 mg/ml and 1-5 mg/ml with molar absorptivity of 2.46Ã—102 L/mol/cm and 4.52Ã—102 L/mol/cm and relative standard deviation of 0.28% and 0.32% for flucloxacillin and trandolapril, respectively. Conclusion: These methods have been successfully applied for the assay of drug in pharmaceutical formulations individually. No interference was observed from common pharmaceutical adjuvants by adopting the proposed method. Keywords: Flucloxacillin, Trandolapril, Extractive spectrophotometry, Bromocresol green.